2020
DOI: 10.1002/jbm.b.34725
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the skin‐implant interface with transcutaneous silver‐coated skin‐and‐bone‐integrated pylon in pig and rabbit dorsum models

Abstract: Implant‐associated soft tissue infections at the skin‐implant interface represent the most frequent complications in reconstructive surgery and lead to implant failures and revisions. Titanium implants with deep porosity, called skin‐and‐bone‐integrated‐pylons (SBIP), allow for skin ingrowth in the morphologically natural direction, thus restoring a reliable dermal barrier and reducing the risk of infection. Silver coating of the SBIP implant surface using physical vapor deposition technique offers the possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
(120 reference statements)
0
5
0
Order By: Relevance
“…Reproduced with permission. [ 213 ] Copyright 2020, John Wiley and Sons. J) A comparison was made between a silver‐coated proximal femur prosthesis explanted 27 months after surgery and a new silver‐coated prosthesis.…”
Section: Silver In Coatingsmentioning
confidence: 99%
“…Reproduced with permission. [ 213 ] Copyright 2020, John Wiley and Sons. J) A comparison was made between a silver‐coated proximal femur prosthesis explanted 27 months after surgery and a new silver‐coated prosthesis.…”
Section: Silver In Coatingsmentioning
confidence: 99%
“…Another method that is being studied through in vivo models is the skin and bone integrated pylon (SBIP) system, an implant with deep pores to promote tissue ingrowth. Preliminary animal studies in both porcine and rabbit models demonstrated tissue ingrowth and the formation of a natural barrier 40 . As a general guiding principle, it is imperative to be judicious when deciding whether to graft bone to the implant interface given the expected donor site morbidity, prolonged surgical time, and the potential infection risk associated with graft harvest and placement 41 .…”
Section: Soft-tissue Closure Of the Residual Limbmentioning
confidence: 99%
“…Metals and their alloys are considered to be the most suitable for replacing damaged supporting bones as compared to polymers and ceramics. Nowadays, Ti and its alloys are especially promising as biocompatible materials due to their strength and physico-chemical resistance, in combination with a relatively low price and density [6]. However, the slow osseointegration of Ti implants still remains a significant problem.…”
Section: Introductionmentioning
confidence: 99%